Iron ore concentrate composite biochar material as well as preparation method and application thereof

Through the composite porous material of iron concentrate and bamboo powder biomass material, it is used to activate persulfate to treat organic wastewater, solving the problem of difficult degradation of antibiotics in water, and achieving efficient pollutant degradation and purification effects.

CN119793460APending Publication Date: 2025-04-11HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411964268.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Antibiotics in water are difficult to degrade, and their degradation efficiency is low, resulting in environmental pollution and ecosystem threats.

Method used

Iron concentrate and bamboo powder biomass materials are calcined under a protective atmosphere to prepare composite porous materials for activation of persulfate treatment of organic wastewater.

Benefits of technology

It improves the degradation efficiency of antibiotic pollutants, has high purification efficiency, simple method and low cost, and provides an environmentally friendly green composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793460A_ABST
    Figure CN119793460A_ABST
Patent Text Reader

Abstract

The invention discloses an iron ore concentrate composite biochar material as well as a preparation method and application thereof, iron ore concentrate and a bamboo powder biomass material are calcined under protective gas, and an iron ore concentrate and bamboo powder biomass composite porous material is prepared. The iron ore concentrate and bamboo powder biomass composite porous material has the characteristics of convenience in production, low cost, high specific surface area, high surface activity, strong magnetism and porosity, is applied to activating persulfate to treat organic wastewater, can catalytically degrade various organic matters in the organic wastewater in a targeted manner, and is high in purification efficiency, simple in method flow and suitable for industrial production. The preparation method is simple, easy to operate, few in required reagent types and low in cost, and is an environment-friendly green composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of antibiotic wastewater treatment, and in particular to an iron concentrate composite biochar material and a preparation method and application thereof. Background Art

[0002] Iron concentrate refers to the concentrate powder obtained by crushing, grinding and beneficiation of natural ore. According to different beneficiation methods, the concentrate powder is divided into various types of concentrate powder, such as magnetic separation, flotation, gravity separation and other concentrate powder. Good iron concentrate pelletizing performance is the basis and prerequisite for producing high-quality pellets. Some research has been carried out in China on how to effectively utilize resources and improve the iron concentrate pelletizing performance.

[0003] How to rationally utilize resources and transform them has become a hot topic today. In this context, biochar came into being. Biochar refers to a type of solid black powdery substance rich in carbon and aromatic compounds that is generated by pyrolysis of biomass (such as straw, tree branches, algae, municipal garbage, etc.) under oxygen-limited or oxygen-free conditions at low or high temperatures (150-1000°C). The preparation methods of biochar include high-temperature pyrolysis, hydrothermal carbonization, and other methods.

[0004] Antibiotics are a type of secondary metabolites produced by microorganisms or higher animals and plants in the course of their lives that have anti-pathogen or other activities and can interfere with the development and function of pathogenic microorganisms. However, livestock and poultry have a low absorption and utilization rate of antibiotics. Only a small amount of antibiotics will be absorbed by the body and converted into non-toxic and harmless substances through hydroxylation, cleavage and glucuronidation in the body. About 60% to 90% will be excreted in the original form with feces and urine. Due to the lack of effective feces and sewage treatment technology or the high cost of investment and operation of facilities, most livestock and poultry feces and urine are directly applied to farmland without treatment, or even directly discharged into water bodies with sewage, resulting in a large amount of unmetabolized antibiotics entering the environment. At present, a large number of studies have shown that antibiotics have acute physiological toxicity to aquatic organisms. Through 226 antibiotic toxicity tests, it was found that 20% of antibiotics are highly toxic to seaweed, 6% of antibiotics are highly toxic to water fleas, about 1 / 3 of antibiotics are highly lethal to fish, and more than 50% of antibiotics are physiologically toxic to fish. Secondly, antibiotics inhibit or even kill certain microorganisms in the environment, affecting the structure of microbial communities. At the same time, antibiotics and their degradation products easily enter the human body through drinking water and food. Long-term drinking and consumption will cause enrichment in the human body, reduce immunity, cause allergic reactions or toxic side effects. In addition, when bacteria are in a low-concentration antibiotic environment for a long time, they will develop drug resistance, induce and spread antibiotic-resistant bacteria "super bacteria", and drug resistance reduces the effectiveness of antibiotics in inhibiting bacterial growth, posing a potential threat to the ecosystem.

[0005] The main purpose of the present invention is to rationally utilize the iron concentrate and bamboo powder biomass materials to improve the application value in the treatment of antibiotic pollutants in water bodies. Summary of the invention

[0006] In order to solve the problem of antibiotics being difficult to degrade and having low degradation efficiency in water, the present invention proposes an iron concentrate composite biochar material and its preparation method and application, wherein iron concentrate and bamboo powder biomass material are calcined under protective gas to prepare a composite porous material. The iron concentrate and bamboo powder biochar composite porous material prepared by the above method is used to activate persulfate to treat organic wastewater.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing an iron concentrate composite biochar material, the method comprising crushing the iron concentrate and bamboo powder biomass (which can be replaced by straw powder, wood powder and other biomass materials) and mixing them, and roasting them under a protective atmosphere to obtain the iron concentrate composite biochar material; wherein the roasting temperature is 500-800° C. After high-temperature roasting, the active components in the biochar may be doped into the iron-based material to form an iron-carbon composite material, which often has high catalytic activity and conductivity, forming a porous structure or a nanocomposite material.

[0009] Preferably, the mass ratio of iron ore concentrate powder to bamboo powder biomass is 1:1-5.

[0010] Preferably, the mixing method is to blend the iron ore concentrate powder and the bamboo powder biomass material by mechanical stirring, or mix them into balls, and then roast them under a protective atmosphere.

[0011] Preferably, the protective atmosphere is nitrogen or argon.

[0012] Preferably, the calcination time is 1-2 hours.

[0013] The present invention also proposes an iron concentrate composite biochar material prepared by the above method.

[0014] The present invention also proposes the use of the iron concentrate composite biochar material prepared according to the above-mentioned preparation method in activating persulfate to treat organic wastewater.

[0015] According to the aforementioned application of the present invention, the application method is as follows: iron concentrate composite biochar material and sodium persulfate are added to the organic wastewater to be tested at the same time, and the removal rate of organic pollutants and TOC removal rate are determined after a period of reaction.

[0016] Preferably, the organic pollutants in the organic wastewater are sulfonamide antibiotics; further, the sulfonamide antibiotic is sulfamethoxazole.

[0017] Compared with the prior art, the beneficial effects of the present invention are embodied in the following aspects:

[0018] 1. Related research has found that persistent free radicals in biochar can activate S2O8 2- Or H2O2 produces active oxygen species, thereby effectively degrading and removing pollutants. However, considering the limited types of surface functional groups and pore structure of biochar and the limitations of preparation conditions, biochar treatment alone can no longer meet the actual water treatment requirements. Adding iron ore concentrate as a composite material can effectively degrade pollutants.

[0019] 2. The iron concentrate composite biochar material of the present invention is used to activate persulfate to treat organic wastewater, and can specifically catalyze and degrade various organic matter in the organic wastewater. It has high purification efficiency, simple method flow, easy operation, few types of reagents required, and low cost. It is an environmentally friendly green composite material.

[0020] 3. Due to the low cost and abundant reserves of iron ore, the study of its degradation performance can not only greatly improve its new application value in the field of environmental protection, but also provide a new low-cost, high-value-added ecological utilization method and idea for the degradation of organic pollutants.

[0021] 4. The present invention provides a porous structure material composed of iron ore concentrate and biochar, which is easy to produce, low in cost, has a high specific surface area, high surface activity, and strong magnetism, and a preparation method thereof BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the XRD diagram of the composite material prepared in Example 1 of the present invention; wherein a is bamboo powder biomass, b is iron ore and bamboo powder biomass composite material (before reaction), and c is iron ore and bamboo powder biomass composite material (after reaction).

[0023] Figure 2 1 is a SEM image of the composite material in Example 1 of the present invention; wherein the scales of each image are: a is 40 μm, b is 500 nm, and c is 2 μm.

[0024] Figure 3 This is a mapping diagram of the composite material in Example 1 of the present invention;

[0025] Figure 4 This is a comparison chart of the degradation rates of sulfamethoxazole by different materials in Application Examples 1-5 of the present invention;

[0026] Figure 5 This is a comparison chart of the degradation rates of sulfamethoxazole by different materials in Application Examples 6-10 of the present invention. DETAILED DESCRIPTION

[0027] Example 1

[0028] The bamboo powder biomass material (Henan Li Ze Environmental Protection Technology Co., Ltd.) was crushed by a high-speed crusher (Wenling Linda Machinery Co., Ltd., model DFY-500C, power 1400W) at 25000r / min for 5min to ensure that the particle size of the small biomass particles reached 30 meshes. The iron concentrate (Anshan Iron and Steel Company Technology Center) was manually crushed for 10min to ensure that the particle size of the small iron concentrate particles reached 800 meshes. The small iron concentrate particles were mixed with the small biomass particles; the mixture was placed in a corundum crucible, deionized water was added, and the mixture was stirred evenly; then Then, the corundum crucible was placed in an oven at 70°C to evaporate the water; then, the corundum crucible was placed in a tubular furnace, N2 was introduced into the tubular furnace at a rate of 30 mL / min, and the air was exhausted for 20 minutes, and then the temperature of the pyrolysis furnace was increased to 800°C at a rate of 10°C / min, and the temperature was maintained at a constant temperature for 60 minutes; after the pyrolysis was completed, N2 was continuously introduced into the pyrolysis furnace until the pyrolysis furnace cooled to room temperature; finally, the product was collected, which was the iron concentrate composite biochar material. The raw material for the preparation of biochar in this preparation process was bamboo powder straw. The mass ratio of bamboo powder biomass material to iron concentrate was 1:2.

[0029] Figure 1 The XRD diagram of the composite porous material prepared in Example 1 of the present invention; wherein a is bamboo powder biomass, b is a composite material of iron ore and bamboo powder biomass (before pyrolysis), and c is a composite material of iron ore and bamboo powder biomass (after pyrolysis). Figure 1 It can be seen that: a The diffraction peak at 2θ value of 22° corresponds to the (002) plane of graphite carbon structure, indicating that biochar is an amorphous structure; b There are five characteristic diffraction peaks of Fe2O3 at 2θ values ​​of 30.36, 35.74, 43.47, 57.51 and 63.71. XRD diffraction analysis proves that bamboo powder biochar has good chemical affinity with iron concentrate.

[0030] Figure 2 The SEM image of the composite material in Example 1 of the present invention; wherein the scales of each image are: a is 40 μm, b is 500 nm, and c is 2 μm. Figure 2 It can be seen that the iron particles are evenly attached to the surface of bamboo powder biochar, forming an iron concentrate composite biomass composite material.

[0031] Figure 3 This is the Mapping diagram of the composite material in Example 1 of the present invention, from Figure 3 It can be seen that the C and Fe of bamboo powder biochar are evenly distributed on the surface of the material.

[0032] Example 2

[0033] The bamboo powder biomass material (Henan Li Ze Environmental Protection Technology Co., Ltd.) was crushed with a high-speed crusher (Wenling Linda Machinery Co., Ltd., model DFY-500C, power 1400W) at 25000r / min for 5min to ensure that the particle size of the small biochar particles reached 30 meshes. The iron ore (Anshan Iron and Steel Company Technology Center) was manually crushed for 10min to ensure that the particle size of the small iron ore particles reached 800 meshes. The small iron ore particles were mixed with the small biomass particles; and placed in a corundum crucible and added Deionized water, stir evenly; then place the corundum crucible in an oven at 70℃ to evaporate the water; then put the corundum crucible into a tube furnace, introduce N2 into the tube furnace, the N2 introduction rate is 30mL / min, exhaust the air time for 20min, and then increase the pyrolysis furnace temperature to 500℃ at a rate of 10℃ / min, and keep the constant temperature for 60min; after the pyrolysis is completed, continue to introduce N2 into the pyrolysis furnace until the pyrolysis furnace cools to room temperature; finally collect the product, which is the iron concentrate composite biochar material. The raw material for the preparation of biochar in this preparation process is bamboo powder straw. The mass ratio of bamboo powder biomass material to iron concentrate is 1:2.

[0034] Example 3

[0035] The bamboo powder biomass material (Henan Li Ze Environmental Protection Technology Co., Ltd.) was crushed with a high-speed crusher (Wenling Linda Machinery Co., Ltd., model DFY-500C, power 1400W) at 25000r / min for 5min to ensure that the particle size of the small biochar particles reached 30 meshes. The iron ore (Anshan Iron and Steel Company Technology Center) was manually crushed for 10min to ensure that the particle size of the small iron ore particles reached 800 meshes. The small iron ore particles were mixed with the small biomass particles; and placed in a corundum crucible and added Deionized water, stir evenly; then place the corundum crucible in an oven at 70℃ to evaporate the water; then put the corundum crucible into a tube furnace, introduce N2 into the tube furnace, the N2 introduction rate is 30mL / min, exhaust the air time for 20min, and then increase the pyrolysis furnace temperature to 600℃ at a rate of 10℃ / min, and keep the constant temperature for 60min; after the pyrolysis is completed, continue to introduce N2 into the pyrolysis furnace until the pyrolysis furnace cools to room temperature; finally collect the product, which is the iron concentrate composite biochar material. The raw material for the preparation of biochar in this preparation process is bamboo powder straw. The mass ratio of bamboo powder biomass material to iron concentrate is 1:2.

[0036] Example 4

[0037] The bamboo powder biomass material (Henan Li Ze Environmental Protection Technology Co., Ltd.) was crushed with a high-speed crusher (Wenling Linda Machinery Co., Ltd., model DFY-500C, power 1400W) at 25000r / min for 5min to ensure that the particle size of the small biochar particles reached 30 meshes. The iron ore (Anshan Iron and Steel Company Technology Center) was manually crushed for 10min to ensure that the particle size of the small iron ore particles reached 800 meshes. The small iron ore particles were mixed with the small biomass particles; and placed in a corundum crucible and added Deionized water, stir evenly; then place the corundum crucible in an oven at 70℃ to evaporate the water; then put the corundum crucible into a tube furnace, introduce N2 into the tube furnace, the N2 introduction rate is 30mL / min, exhaust the air time for 20min, and then increase the pyrolysis furnace temperature to 700℃ at a rate of 10℃ / min, and keep the constant temperature for 60min; after the pyrolysis is completed, continue to introduce N2 into the pyrolysis furnace until the pyrolysis furnace cools to room temperature; finally collect the product, which is the iron concentrate composite biochar material. The raw material for the preparation of biochar in this preparation process is bamboo powder straw. The mass ratio of bamboo powder biomass material to iron concentrate is 1:2.

[0038] Example 5

[0039] The bamboo powder biomass material (Henan Li Ze Environmental Protection Technology Co., Ltd.) was crushed with a high-speed crusher (Wenling Linda Machinery Co., Ltd., model DFY-500C, power 1400W) at 25000r / min for 5min to ensure that the particle size of the small biochar particles reached 30 meshes. The iron ore (Anshan Iron and Steel Company Technology Center) was manually crushed for 10min to ensure that the particle size of the small iron ore particles reached 800 meshes. The small iron ore particles were mixed with the small biomass particles; and placed in a corundum crucible and added Deionized water, stir evenly; then place the corundum crucible in an oven at 70℃ to evaporate the water; then put the corundum crucible into a tube furnace, introduce N2 into the tube furnace, the N2 introduction rate is 30mL / min, exhaust the air time for 20min, and then increase the pyrolysis furnace temperature to 900℃ at a rate of 10℃ / min, and keep the constant temperature for 60min; after the pyrolysis is completed, continue to introduce N2 into the pyrolysis furnace until the pyrolysis furnace cools to room temperature; finally collect the product, which is the iron concentrate composite biochar material. The raw material for preparing biochar in this preparation process is bamboo powder straw. The mass ratio of bamboo powder biomass material to iron concentrate is 1:2.

[0040] Application Example 1

[0041] Catalytic degradation of sulfamethoxazole in water treatment

[0042] Experimental steps: Add the organic wastewater samples to be tested with sulfamethoxazole concentrations of 20 mg / L, 40 mg / L, and 60 mg / L into 100 mL of surface water.

[0043] 0.3 g of the iron concentrate composite biochar material prepared by the method of Example 1 and 0.3 g of sodium persulfate were added to the organic wastewater to be tested. The sulfamethoxazole removal rate and TOC removal rate after 5 min and 30 min of treatment reaction were recorded as Application Example 1;

[0044] 0.3 g of the iron concentrate composite biochar material prepared by the method of Example 1 was added to the organic wastewater to be tested. The sulfamethoxazole removal rate and TOC removal rate after 5 min and 30 min of treatment were recorded as blank 1;

[0045] 0.3g sodium persulfate was added to the organic wastewater to be tested, and the removal rate of sulfamethoxazole and TOC after 5min and 30min treatment reaction was recorded as blank 2;

[0046] The results are shown in Tables 1 and 2

[0047] Table 1

[0048]

[0049] Table 2

[0050] TOC removal rate (5min) TOC removal rate (30min) unit % % Application Example 1 50 100 Blank 1 0 0 Blank 2 0 0

[0051] It can be seen from Table 1 and Table 2 that the removal rate of sulfamethoxazole by the iron concentrate composite material reached 100% in 30 minutes, and the removal rate of TOC also reached 100% in 30 minutes.

[0052] Application Example 2-5

[0053] 0.3 g of the iron concentrate composite biochar material prepared by the methods of Examples 2, 3, 4, and 5 was added to the above 20 mg / L sulfamethoxazole water sample, and the organic wastewater sample was treated under the same persulfate dosage and discharge conditions as in Application Example 1. The degradation rate of sulfamethoxazole after 5 min and 30 min of treatment reaction was recorded as Application Example 2-5;

[0054] Figure 4 This is a comparison chart of the degradation rates of sulfamethoxazole by different materials in Application Examples 1-5 of the present invention.

[0055] Depend on Figure 4 It can be seen that when the mass ratio of bamboo powder biomass material to iron concentrate is controlled to be 1:2, the iron concentrate composite biochar material prepared at 800°C has the best degradation rate of organic pollutant sulfamethoxazole. When the temperature is 900°C, the degradation performance decreases significantly.

[0056] In order to better determine the degradation performance of the iron concentrate composite biochar material of the present invention, the degradation rate of the composite material of the present invention and a series of comparative experimental groups were determined, and the specific raw material composition of the determination group was determined.

[0057] Application Example 6: 0.5 g of iron ore concentrate + 0.5 g of biomass material; (processed according to the method described in Example 1 of the present invention)

[0058] Application Example 7: 0.5 g of iron ore concentrate + 1 g of biomass material; (processed according to the method described in Example 1 of the present invention)

[0059] Application Example 8: 0.5 g of iron ore concentrate + 1.5 g of biomass material; (processed according to the method described in Example 1 of the present invention)

[0060] Application Example 9: 0.5 g of iron ore concentrate + 2 g of biomass material; (processed according to the method described in Example 1 of the present invention)

[0061] Application Example 10: 0.5 g of iron ore concentrate + 2.5 g of biomass material; (processed according to the method described in Example 1 of the present invention) Figure 5 The figure is a comparison chart of the degradation rate of sulfamethoxazole by different materials of the present invention.

[0062] from Figure 5 It can be seen that when the ratio of iron ore concentrate to bamboo powder biochar is 1:3, the degradation effect is the best, reaching 100%.

Claims

1. A method for preparing an iron concentrate composite biochar material, characterized in that: The iron concentrate and bamboo powder biomass are crushed and mixed, and then roasted under a protective atmosphere to obtain the iron concentrate composite biochar material; the roasting temperature is 500-800°C.

2. The method for preparing the iron concentrate composite biochar material according to claim 1, characterized in that: The mass ratio of the iron ore concentrate to the bamboo powder biomass is 1:1-5.

3. The method for preparing the iron concentrate composite biochar material according to claim 1, characterized in that: The mixing method is mechanical stirring and blending or mixing into balls.

4. The method for preparing the iron concentrate composite biochar material according to claim 1, characterized in that: The protective atmosphere is nitrogen or argon.

5. The method for preparing the iron concentrate composite biochar material according to claim 1, characterized in that: The calcination time is 1-2h.

6. The iron concentrate composite biochar material prepared according to the preparation method according to any one of claims 1 to 5.

7. Use of the iron concentrate composite biochar material according to claim 6 in activating persulfate to treat organic wastewater.

8. The use according to claim 7, characterized in that: The application method is as follows: iron concentrate composite biochar material and persulfate are added to the organic wastewater to be tested at the same time, and the removal rate of organic pollutants and TOC removal rate are determined after a period of reaction.

9. The use according to claim 8, characterized in that: The organic pollutants in the organic wastewater are sulfonamide antibiotics.

10. The use according to claim 9, characterized in that: The sulfonamide antibiotic is sulfamethoxazole.